4-AP-3-MeOH Promotes Structural and Functional Spontaneous Recovery in the Acute Sciatic Nerve Stretch Injury. Issue 1 (20th January 2020) - Chen, Yan; Wang, Weidong; Zhao, Zhimin; Ren, Dong; Xin, Danmou
Background: 4-AP-3-MeOH, a derivative of 4-aminopyridine, was developed and demonstrated to prevent nerve pulse diffusion due to myelin damage and significantly enhance axonal conduction following nerve injury. Currently, repurposing the existing drug such as 4-AP-3-MeOH to restore motor function is a promising and potential therapy of peripheral nerve injury. However, to evaluate drug effect on sciatic nerve injury is full of challenge. Methods: Sciatic functional index was used to determine and measure the walking track in the stretch injury model. Nerve conductivity was performed by electrical stimulation of a nerve and recording the compound muscle action potential. Myelin thickness and regeneration was imaged and measured with transmission electron microscopy (TEM). Results: In this study, we developed a sciatic nerve injury model to minimize the spontaneous recovery mechanism and found that 4-AP-3-MeOH not only improved walking ability of the animals but also reduced the sensitivity to thermal stimulus. More interesting, 4-AP-3-MeOH enhanced and recovered electric conductivity of injured nerve; our TEM results indicated that the axon sheath thickness was increased and myelin was regenerated, which was an important evidence to support the recovery of injured nerve conductivity with 4-AP-3-MeOH treatment. Conclusions: In summary, our studies suggest that 4-AP-3-MeOH is a viable and promising approach to the therapy of peripheral nerve injury and in support of repurposing the existing drug to restore motor function.